Ultrasmall Pd/Au bimetallic nanocrystals embedded in hydrogen-bonded supramolecular structures: facile synthesis and catalytic activities in the reduction of 4-nitrophenol1. Issue 38 (14th October 2015) - Jiang, Feng; Li, Ruimin; Cai, Jianhua; Xu, Wei; Cao, Anmin; Chen, Daiqin; Zhang, Xing; Wang, Chunru; Shu, Chunying
<x xml:space="preserve">Abstract</x> A hydrogen-bonded supramolecular structure supported with ultrasmall Au, Pd bimetallic nanoparticles was readily synthesized and showed unusual catalytic properties.